2012
DOI: 10.1017/s0003055411000475
|View full text |Cite
|
Sign up to set email alerts
|

The Perils of Unearned Foreign Income: Aid, Remittances, and Government Survival

Abstract: G iven their political incentives, governments in more autocratic polities can strategically channel unearned government and household income in the form of foreign aid and remittances to finance patronage, which extends their tenure in political office. I substantiate this claim with duration models of government turnover for a sample of 97 countries between 1975 and 2004. Unearned foreign income received in more autocratic countries reduces the likelihood of government turnover, regime collapse, and outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(200 citation statements)
references
References 38 publications
7
192
1
Order By: Relevance
“…Singer (2010 finds that inflowing remittances affect exchange-rate regimes, and hence provides evidence that policy in receiving countries is responsive to incoming remittances. Moreover, recent research demonstrates that remittances also have detrimental effects on the institutional quality of receiving countries ), as they can weaken governance by increasing levels of corruption (Ahmed 2012;Ahmed 2013;Berdiev et al 2013) and crowd out public spending on education and health (Ebeke 2012).…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Singer (2010 finds that inflowing remittances affect exchange-rate regimes, and hence provides evidence that policy in receiving countries is responsive to incoming remittances. Moreover, recent research demonstrates that remittances also have detrimental effects on the institutional quality of receiving countries ), as they can weaken governance by increasing levels of corruption (Ahmed 2012;Ahmed 2013;Berdiev et al 2013) and crowd out public spending on education and health (Ebeke 2012).…”
Section: Relevant Literaturementioning
confidence: 99%
“…These large monetary inflows affect microand macroeconomic outcomes in the receiving countries. For example, the literature has demonstrated that remittances affect the quality of governance (Ahmed 2012;Ahmed 2013;Berdiev et al 2013), financial sector development (Giuliano and Ruiz-Arranz 2009;Aggarwal et al 2011), exchange rate regimes (Singer 2010), international competitiveness (López et al 2008;Acosta et al 2009) and schooling decisions (Edwards and Ureta 2003;Alcaraz et al 2012;Ambler et al 2015). 1 Despite their enormous importance, little research exists on the relevance and impact of inflowing remittances for public finances of receiving countries.…”
Section: Introductionmentioning
confidence: 99%
“…Results also contribute to debates of how private safety nets affect governance in illiberal democracies. By documenting selfinsurance effects on government approval across a range of liberal and illiberal democracies, we offer a an important individual-level explanation of how private safety nets, be it in the form of savings, or help from friends and relatives, could help extend government tenure (Ahmed 2012). More specifically, findings suggest that self-insurance could extend tenure not only by dampening demand for redistribution, but also by ameliorating government approval, even when economic performance is poor.…”
Section: Resultsmentioning
confidence: 99%
“…Cheng and Gereffi 1994;Diaz 1993;Meagher 1995, Greskovits 1998. In recent years, Ahmed (2012Ahmed ( , 2017 has provided compelling evidence that far from empowering political mobilization (De la Garza and Hazan 2003), private safety nets in the form of unearned foreign income can reduce government turnover. While this literature recognises self-insurance effects on government stability, we still know relatively little about the microlevel mechanisms that drive the political consequences of self-insurance and could influence the connection between household safety nets and political support.…”
Section: The Importance Of Self-insurancementioning
confidence: 99%
“…As noted by Castel-Branco (2008), in a case study on aiddependency in Mozambique, aid-recipient governments, like many governments, are motivated by an interest in their own survival and will use aid first in this pursuit and second in the pursuit of responsible public expenditure. That aid can be used to finance patronage has been shown yet again in Ahmed (2012) and using aid in this way may foster petty corruption, nepotism and favouritism that can undermine governance quality.…”
Section: What Do We Know About Aid and Governance?mentioning
confidence: 98%